THE PSYCHOANALYTIC AND INTERRACIAL VIEWPOINT IN “MY HUMPS” MUSIC VIDEO - Ayuningtyas, Yanlita Frenty (LANTERN (Journal on English Language, Culture and Literature), 2017)
"My Humps" is a song by The Black Eyed Peas. The lyrics and the music video tell about the relationship between the man (Will.i.am) with the woman (Fergie), who Will.i.am always flirts with Fergie and always asks her for dating. Although Fergie always refuses him but she also flirts the man to show off her sexy body. The purpose of this study is to analyze the poetic elements in the lyrics and to show the readers the psychological contents, as portrayed in the music video. This study uses textual and contextual theories to analyze the data. Meanwhile, close reading, close listening, and close viewingas research method are used to compile the object of “My Humps” music video. The content of this study is the existence of psychoanalysis through Sigmund Freud’s theory in American hip-hop music included id, ego,superego, defense mechanism, psychosexual, and interracial viewpoint reflected in lyrics and scenes in the music video of "My Humps".